Spiritual emotional freedom technique and level anxiety among people with pre-percutaneous coronary intervention - Inggriane Puspita Dewi; Izzaniar Purwanti; Perla Yualita (Universitas Muhammadiyah Malang, 2024)
Introductions: Percutaneous Coronary Intervention is a low-risk diagnostic procedure, but many patients experience a high level of anxiety. Objectives: The purpose of the study was to determine the effect of SEFT on the anxiety level among people with Pre- Percutaneous Coronary Intervention. Methods: The research design used a quasi-experiment with a pretest-posttest design with a control group design.  The number of samples used G-Power with nonprobability sampling was as many as 18 people in each group (a total of 36 people). The inclusion criteria are elective inpatients, patients diagnosed with CAD who have anxiety and are able to communicate, patients indicated as primary care, and patients with complications and panic are excluded, SEFT consists of set-up, tune-in, and tapping given one hour before cardiac catheterization for 15-25 minutes with two repetitions. Questionnaires for measuring anxiety levels before and after therapy using the Hamilton Scale for Anxiety (HARS) with validity (r count 0.57-0.97) and reliability (0.93-0.97). The analysis used Mann-Whitney. Results: The short version of SEFT in the control group (p-value 0.001) and the long version of SEFT in the intervention group (p-value <0.001) were proven to have an effect on reducing anxiety scores.  there was no difference in the mean anxiety scores between the groups given the long version and the short version of the SEFT intervention (p-value 0,053). Conclusion: The conclusion of the study showed the effect of SEFT therapy on the anxiety of cardiac pre-catheterization patients. SEFT can be a complementary nursing therapy to reduce anxiety.